PERAN SEKRETARIAT DPRD DALAM MENDUKUNG FUNGSI DPRD (STUDI DI KANTOR SEKRETARIAT DPRD KABUPATEN ROTE NDAO) - Lay, Jesica Magdalena; Wadu, Jacob; Long , Belandina L.; Nursalam, Nursalam (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
Role is the behavior or behavior of a person or group in carrying out the duties of the position or position that is carried out. The role of the DPRD Secretariat is how to carry out its duties and functions in supporting the functions of the DPRD. This research aims to analyze the role of the DPRD Secretariat in supporting the functions of the Rote Ndao Regency DPRD. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The types and sources of data obtained are primary data and secondary data. The results showed that the role of the DPRD Secretariat was not maximized in supporting the function of the Rote Ndao Regency DPRD. The main obstacles faced are the limited number of employees, budget, infrastructure, and staff skills in supporting administrative digitization. This has an impact on the slow work process and less than optimal service to the DPRD. Therefore, an increase in resources is needed to realize a better role of the DPRD Secretariat.